Application of neurofuzzy in the develoment of road bump designs (2007)
"This contribution is on the development of a neurofuzzy model that aids in capturing imprecision and uncertainty in the. various road bump parameters. Road bumps are structures built on roads to act as obstructions to vehicles plying these roads. The neurofuzzy methodology is used to check the vehicle speeds to acceptable standards. Particular use is made of neurofuzzy since it is an improvement on the traditional model proposed earlier in the literature. The work is motivated by the need for a more reliable and easily understandable methodology that guides decision makers in making correct decisions in a timely manner The results obtained demonstrate that it is feasible to apply the model in practice. The paper is new in that it proposes a novel approach to quantifying the results of road bump design in order to achieve worthy and reliable result. "